Resiko Ulkus Kaki Dabetes pada Petani di Madura Indonesia - Rofiqi, Muhammad; Sutawardana, Jon Hafan; Kushariadi, Kushariadi (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
A diabetic foot ulcer is one of the diabetes mellitus complications. The farmer is a job that has a risk for developing diabetic ulcers, especially farmers with diabetes. Farmers pay less attention to protecting their feet, so they risk foot trauma. This study aimed to describe the risk of diabetic foot ulcers in farmers. This was a descriptive observational study conducted at the Palengaan Pamekasan Health Center working area. As many as 76 respondents were chosen using the purposive sampling technique. All respondents were examined using inlow's 60-second diabetic foot instrument. The data were analyzed with univariate analysis. This study found that 72.4% of farmers had a moderate risk of developing diabetic ulcers, and 11,8% of patients were at risk for severe foot ulcers. This data showed that most farmers are at high risk of developing diabetic foot ulcers. Therefore, farmers with diabetes need intensive attention from medical practitioners to provide education on the importance of foot protection while working.